Effect of Reinforcement Corrosion on Structural Behavior in Reinforced Concrete Structures According to Initiation and Propagation Periods - Seda Akduman; Hakan Öztürk (Buildings)
Reinforced concrete (RC) structures lose performance over time. One of the most significant environmental factors causing performance degradation is reinforcement corrosion. Corrosion reduces the diameter of the reinforcement and degrades the mechanical properties of both the concrete and the steel. In order to determine the degradation of the structural performance caused by corrosion, it is essential to identify the time periods in which corrosion initiates and propagates, and to thoroughly analyze the parameters that govern these processes. In this study, the corrosion initiation and propagation times were calculated separately for an RC frame exposed to chloride ions. Factors contributing to the further reduction of these processes were identified. Analyses and comparisons were made to determine the structural performance of the calculated RC frame over its service life. The results showed that corrosion reduces the structural performance, especially in regions with high seismic potential, where preventive measures against corrosion are essential. The most important parameter influencing the corrosion mechanism is the corrosion rate, while another important factor is the formation of cracks on the element surface. In cases where cracks are present, the corrosion initiation time is shortened, which means that materials should be selected at the design stage that are suitable for the environment, and the years of maintenance required should be calculated by the design engineers. In addition, the surfaces of RC elements should be monitored, and crack tracking should be carried out.